التحولات الإقتصادية والإجتماعية والثقافية في وادي سوف من خلال الوثائق الأرشيفية 1954 ـ 1962 - بوراس, طليبة (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: يدرس الموضوع التحوّلات الاقتصادية والاجتماعية والثقافية في وادي سوف خلال فترة الثورة التحريرية 1954-1962، حيث أن مجتمع وادي سوف ﺷﺄنه ﺷﺄن بقية مكونات المجتمع الجزائري الأخرى، عرف خلال فترة الثورة التحريرية تغيرات وتحولات مختلفة ﻓﻲ فترة زمنية محدودة تحت تأثير عوامل متعددة ومؤثرة، دفعت بالمجتمع إﻟﻰ التكيّف والتحول إﻟﻰ مسايرة هذه اﻷوﺿﺎع الطارئة، سعيا منه لتفادي أسوأ النتائج، والتخفيف من تبعاتها، والتطلع إﻟﻰ التأقلم مع التحوﻻت المتتالية التي تختلف عمّا شهده ﻓﻲ الفترات السابقة، حيث تراكمت مشاغل المواطن البسيط وتجاذبتها تحديات كثيرة ﻋﻠﻰ مختلف الأصعدة؛ اقتصادية واجتماعية وثقافية، ولم تظهر بوادر الانفراج إﻻ بعد الاستقلال، لذلك حاولت الدراسة رصد تلك التحولات والوقوف على تطوراتها من خلال البحث والتقصي في مختلف الوثائق الأرشيفية والمصادر التاريخية. Résumé : The subject studies the economic, social and cultural transformations in Oued Souf during the period of the Liberation Revolution of 1954-1962, as the community of Oued Souf, like the rest of the other components of Algerian society, experienced during the period of the Liberation Revolution various changes and transformations in a limited period of time under the influence of multiple and influential factors that pushed society To adapt and shift to keeping pace with these emergency situations, in an effort to avoid the worst outcomes, mitigate their consequences, and aspire to adapt to successive transformations that differ from what he witnessed in previous periods, where the concerns of the ordinary citizen accumulated and were attracted by many challenges at various levels; Economic, social and cultural, and signs of relief did not appear until after independence. Therefore, the study attempted to monitor these transformations and determine their developments through research and investigation into various archival documents and historical sources.
أطروحة دكتوراه تخصص تاريخ حديث ومعاصر في العلوم الإجتماعية و الإنسانية
Keywords: وادي سوف، التحولات، الإقتصادية، الإجتماعية، الثقافية، السياسة الإستعمارية، الثورة التحريرية; Oued Souf, economic, social, cultural transformations, colonial policy, liberation revolution.